The Influence of Interpersonal Communication Interactions between Lecturers and Students on Student Learning Achievement - Algifari, Rama Dwi; Yudistira, Adam; Setiawan, Budi; Nughraha, Tegar Adhi (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2022)
Communication can help efforts to achieve educational goals, in the world of education it is closely related to communication between lecturers and students, so effective communication is needed, but in reality effective communication does not occur due to limited time or lack of knowledge in delivering communication effectively. This research aims to analyze the influence of interpersonal communication interactions between lecturers and students on student learning achievement in class 3A5 Fikom, Bhayangkara University. The research method used is a survey research method with a descriptive quantitative approach. The population of this study were all students from the Faculty of Communication Sciences, Bhayangkara University, Jakarta Raya. Sampling used non-probability sampling and a convenience sampling type approach, namely by making respondents available,30 people as respondents. Based on the search results via SPSS 26.0, the results of the hypothesis test were obtained, stating that F count > F table (1,299 > 0,026), namely that there is a linear relationship between the independent variable (X) and the dependent variable (Y), which means there is an interaction effect. interpersonal communication between lecturers and students on student learning achievement.